A cross-sectional review of the prevalence of integrative medicine in pediatric pain clinics across the United States. (June 2018) - Bodner, Kristen; D'Amico, Salvatore; Luo, Man; Sommers, Elizabeth; Goldstein, Laura; Neri, Caitlin; Gardiner, Paula
Highlights: Children living in rural areas specifically in Southern United States have very limited access to IM therapies within PPCs. Non-profit PPCs were more likely to staff IM providers compared to private PPCs. Mind-body exercises are the most common IM services offered in PPCs with IM. Abstract: Purpose: This project assesses the prevalence of integrative medicine (IM) in pediatric pain clinics (PPCs) across the United States. Methods: PPCs were identified through the American Pain Society and cross referenced through the International Association for the Study of Pain (IASP). A cross-sectional review using each PPC's website was then utilized for further information. We collected data regarding each program's target population, non-profit status (where non-profits were designated as hospitals that do not operate for-profit purpose, and private as institutions receiving private funding), location, services provided and participating providers. Descriptive statistics were used for data analysis. Results: Of the 53 PPCs identified, 43 (81%) were part of a non-profit healthcare organization, and 10 (19%) were within a private hospital; 85% were located in urban settings, 15% in rural settings; 83% were located in free-standing children's hospitals. Thirty-two (60%) PPCs utilized IM, including acupuncture (38%), mind-body (21%), massage (21%), aromatherapy (19%), nutrition counseling (17%) and/or art/music therapy (11%). The most prevalent providers within PPCs offering IM were yoga instructors (84%), nutritionists (56%) and mind-body specialists (44%). IM was offered in 63% of programs in non-profit organizations and 50% in private hospitals; 58% of urban sites and 75% of rural sites. Within each region, 91% (n = 10) of PPCs in the West offer IM, 53% of PPCs in the Midwest (n = 10) and Northeast (n = 8) offer IM and 50% (n = 4) of PPCs in the South offer IM compared to PPCs who do not. Conclusions: Of 53 current identified PPCs, over half offer IM services. While children in the US are more likely to find a PPC offering IM services, access to do so is more limited in rural and southern regions.